(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of this work is to determine the changes in the bacterial community structure in transgenic maize crops as well as their impact on other plants. The methodology used consisted of a search for original publications in four databases and their subsequent filtering by inclusion and exclusion criteria. In the results, a total of 15 articles were obtained, 13 of which compared a transgenic corn with its hybrid or wild counterpart in its rhizosphere and endosphere composition and the changes that these presented; on the other hand, 2 of these articles mentioned the crossbreeding that may exist between a transgenic crop and a non-transgenic one due to their type of pollination. In conclusion, the changes found in the rhizosphere and endosphere are not significant and are due to a process of adaptation of the microorganisms, and there must be minimum standards for growing transgenic corn to protect non-transgenic species.